Tensions Between Envisioned Aims and Enacted Practices in the Teaching of Muslim Young Adult Literature. Issue 2 (February 2020) - Glenn, Wendy J.; Ginsberg, Ricki
Context: Research notes the repeated existence of a disconnect between teachers' aims and practices, particularly when their work is done in communities with significant numbers of students who are minoritized by dominant societal norms. Simply wanting to do this work is not enough and can result in harm to students and the communities they inhabit. Research Question: How does a teacher envision instructional aims and enact classroom practices as she infuses young adult literature with Muslim characters and content into her curriculum? Setting: Freshman classroom in a diverse school community in the northeastern United States. Participant: This study examines the thinking and teaching practices of one classroom teacher. It focuses on how the findings have resonance and transferability for other scholars who are studying the phenomenon and who seek to use the findings as a model to conduct related research. Practice: During 10 weeks as a regular part of their English course experience, one class of freshman students read and discussed young adult novels that contain Islam-related content and a Muslim protagonist. The classroom teacher facilitated the sessions. At least one university researcher on the project attended one class session each week to observe and collect data. Research Design: This qualitative study uses an inductive methodological approach to establish clear links between the raw data and research question in systematic and iterative ways. Data Collection: Data sources from the 10-week instructional period included: four semi-structured participant interviews (one prior to the start of instruction, two during the instructional period, and one following instruction); 16 weekday reflections generated by the participant; and 10 weekly classroom observations conducted by the research team. Findings: While the teacher had clear purposes for her instruction of the texts, her enacted practices did not always align with or result in the attainment of her goals. The teacher's aims of being a teacher expert conflicted with practices that rationalized a lack of the knowledge necessary to enact this role. And the teacher's aim of teaching for equity and justice clashed with her practices, which reflected a valuing of safety over conflict. Conclusions: The study intimates the inadequacy of simply wanting to teach less familiar cultural content and argues that an anticipation of cognitive dissonance seems essential to determining culturally responsive aims that are strongly connected to enacted practices as teachers choose to bravely navigate unfamiliar territories.